2016
DOI: 10.1186/s13059-016-1084-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of genetic data sets reveals a shared innate immune component in autism spectrum disorder and its co-morbidities

Abstract: BackgroundAutism spectrum disorder (ASD) is a common neurodevelopmental disorder that tends to co-occur with other diseases, including asthma, inflammatory bowel disease, infections, cerebral palsy, dilated cardiomyopathy, muscular dystrophy, and schizophrenia. However, the molecular basis of this co-occurrence, and whether it is due to a shared component that influences both pathophysiology and environmental triggering of illness, has not been elucidated. To address this, we deploy a three-tiered transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 113 publications
3
38
0
Order By: Relevance
“…Given the high prevalence of ASD and the extra challenges facing individuals with the condition, it is important to identify with which comorbidities ASD is associated. Individuals with ASD have higher rates of comorbidities including a number of autoimmune diseases [11][12][13][14][15][16][17][18][19]. Some of these studies have shown an increased prevalence of ASD in children with Type 1 diabetes compared with the general population, whereas others have shown no difference.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high prevalence of ASD and the extra challenges facing individuals with the condition, it is important to identify with which comorbidities ASD is associated. Individuals with ASD have higher rates of comorbidities including a number of autoimmune diseases [11][12][13][14][15][16][17][18][19]. Some of these studies have shown an increased prevalence of ASD in children with Type 1 diabetes compared with the general population, whereas others have shown no difference.…”
Section: Introductionmentioning
confidence: 99%
“…Of the APP studied, CRP had the strongest association with risk of ASD in the case-control comparison, displaying a U-shaped association with odds of ASD. While the shape of the association between CRP and odds of ASD in the sibling comparison was similar, the association was less apparent with considerably wider confidence intervals in the sibling analysis, possibly reflecting shared common genetic variation in innate immune signaling and risk of ASD (8). We also observed a weaker relationship between CRP and risk of ASD among those whose mothers had a previous history of psychiatric illness in the case-control comparison, with a significant interaction detected between maternal psychiatric history and levels of CRP.…”
Section: Discussionmentioning
confidence: 88%
“…Peripheral concentrations of cytokines and chemokines involved in the innate and adaptive immune responses vary in individuals already diagnosed with ASD compared to controls (3,4), though the prevalence of multiple disorders of the immune system (e.g., asthma, infections, allergy, autoimmune disorders) is also higher in individuals with ASD (5)(6)(7). Integrative analyses of genetic and transcriptomic data suggest that ASD and several of these commonly co-occurring conditions may be related via shared mechanisms involving innate immunity (8).…”
Section: Introductionmentioning
confidence: 99%
“…Co-occurrence of ASD with disorders with immunological aetiology is widely reported in the literature. A recent molecular genetic study revealed shared immune components between ASD and multiple co-morbid medical disorders 7 . It has also been proposed that autism is based on immune mediated mechanisms and implicates the possibility of an aetiological association between bronchial asthma and autism 8 .…”
Section: Discussionmentioning
confidence: 99%